Sharia Compliance of Crowdfunding Platforms for MSME Financing in Indonesia - Iman, Tsubutul; Mustofa, Mustofa; Tantriana, Deasy; Mugiyati, Mugiyati (UIN Siber Syekh Nurjati Cirebon, 2025)
The rapid development of financial technology has introduced sharia crowdfunding as an alternative financing instrument for Micro, Small, and Medium Enterprises (MSMEs) that face limited access to conventional banking services. This study aims to examine the extent to which sharia crowdfunding platforms in Indonesia comply with Islamic economic principles, particularly in relation to contract structures, operational mechanisms, and alignment with maqāṣid al-Sharī‘ah. This research employs a qualitative normative–empirical approach using document analysis of DSN–MUI fatwas, regulatory frameworks issued by the Financial Services Authority (OJK), and operational disclosures of licensed sharia crowdfunding platforms. The findings indicate that most platforms have adopted sharia-compliant contracts such as mudhārabah, musyārakah, and qard al-ḥasan, which structurally eliminate elements of ribā, gharar, and maysir. From a maqāṣid perspective, sharia crowdfunding contributes to the protection of wealth (ḥifẓ al-māl), promotes economic justice, and enhances financial inclusion for MSMEs. However, substantive challenges remain, particularly regarding limited sharia financial literacy among MSME actors, uneven implementation of transparency standards, and potential moral hazard risks in fund utilization. This study contributes to Islamic economic scholarship by positioning sharia crowdfunding not merely as a digital financial innovation, but as an instrument of MSME empowerment that must be evaluated through both regulatory compliance and maqāṣid-oriented ethical outcomes. The findings provide policy-relevant insights for regulators, platform providers, and Islamic finance stakeholders in strengthening a sustainable and justice-based sharia crowdfunding ecosystem.Keywords: Sharia crowdfunding; MSME financing; Islamic economic law; maqāṣid al-Sharī‘ah; sharia fintech